Short Stature and Motor Development in Children Aged 2-5 Years Old - Hilarius, Sancha M; Pangemanan, Lisa; Djaputra, Edith Maria (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Background: Short stature is defined as a child’s height below < –2 SD based on age. Epidemiologic data shows a high percentage of Indonesian toddlers with short stature. There is fast motoric development in children above two years old. If there is a disruption in motor development, the impact will have a long-term effect on growth and development. Aim: This research aimed to determine the relationship between short stature and motor development in children aged 2-5 years. Method: This study used an observational analytic method with cross-sectional design and consecutive sampling techniques. There were 236 subjects in this study. Height was measured by stadiometer and short stature assessed by the WHO growth Chart, while the motor development was assessed using KPSP (Kuesioner Pra Skrining Perkembangan). ChiSquare test was used to analyze the data (α= 0.05). Results: Relationship between short stature and motor development variables showed a significant weak correlation (P = 0,000; phi = 0,377) in children aged 2-5 years. Conclusion: Short stature has a weak significant relationship with the motor development in children aged 2-5 years old.